Pengaruh Ukuran Perusahaan, Profitabilitas, dan Leverage terhadap Manajemen Laba Pada Perusahaan Manufaktur - Ni Made Rianita (ARTHA SATYA DHARMA, 2021)
The purpose of this study was to determine the effect of firm size, profitability, and leverage on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The sample of this study were 16 manufacturing companies listed on the Indonesia Stock Exchange (IDX). The method of data collection was carried out using a study of documentation obtained from the website www.idx.co.id. The data analysis method used is multiple regression analysis. The results show that: (1) company size has a significant effect on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020 with a Significance value (Sig) of the company size variable < 0.05 (0.031 < 0, 05), profitability has a significant effect on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020 with a significance value (Sig) of the profitability variable < 0.05 (0.000 < 0.05), leverage has a significant effect on earnings management in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2018-2020 with a significance value (Sig) of the leverage variable < 0.05 (0.021 < 0.05), and company size, profitability, and leverage simultaneously have an effect on significant to earnings management with a significance value (Sig) < 0.05 (0.000 < 0.05).